Analysis of linear accelerator-based fractionated stereotactic radiotherapy in brain metastases: efficacy, safety, and dose tolerances - Li, Yuhong; Ma, Huiying; Hua, Rui; Wang, Tingting; Ding, Naixin; Deng, Liping; Lu, Xiaomin; Chen, Wei (Frontiers in Oncology, 2024)
ObjectiveTo assess the efficacy and safety of linear accelerator-based fractionated stereotactic radiotherapy (LINAC-FSRT) in patients with brain metastases (BM).MethodsWe retrospectively analyzed 214 patients treated with LINAC-FSRT, categorized based on biologically effective dose (BED10, α/β = 10) into two groups (≤55 Gy, >55 Gy). Stratified analyses were conducted based on targeted therapy to compare survival outcomes. To examine brain tissue dose-tolerance volume, patients were divided into two groups: the standard Hypofractionated Treatment Effects in the Clinic (HyTEC) protocol group and an adjusted HyTEC protocol group where dose-volume restrictions exclude the planning target volume (PTV).ResultsResults as of December 2023 showed median intracranial progression-free survival (iPFS) at 12.4 months, with median overall survival (OS) not reached and a one-year local control (LC) rate of 68.7%. Mild to moderate toxicity affected 17.3% of patients, while severe toxicity occurred in 2.8%. Multivariate Cox analysis indicated that uncontrolled extracranial disease significantly reduced iPFS (HR = 2.692, 95%CI:1.880–3.853, P < 0.001) and OS (HR = 3.063, 95%CI:1.987–4.722, P < 0.001). BED10 >55 Gy (HR = 0.656, 95%CI:0.431–0.998, P = 0.049) improved OS, showing statistical significance (P = 0.037) without affecting iPFS or CNS toxicity (P = 0.127, P = 0.091). Stratified analysis highlighted nearly significant OS improvements with high-dose FSRT and targeted therapy (P = 0.054), while concurrent therapy markedly enhanced iPFS (P = 0.027). No significant differences were observed in intracranial local failure (ILF—which represents progression in previously treated areas during follow-up), one-year LC rates, iPFS, or OS between dose-volume groups. Adjusting HyTEC volume restrictions did not significantly increase CNS adverse reactions (P = 0.889).ConclusionsLINAC-FSRT is safe and effective in BM. BED10>55 Gy notably enhances OS post-LINAC-FSRT and may benefit LC. High BED10 FSRT with targeted therapy likely boosts synergy, and concurrent targeted therapy significantly improves iPFS. Diminishing dose volume constraints at different fractions based on the HyTEC guidelines is feasible.